Reactions to Brexit in images: a multimodal content analysis of shared visual content on Flickr. (February 2021) - Bouko, Catherine; De Wilde, July; Decock, Sofie; De Clercq, Orphée; Manchia, Valentina; Garcia, David
In this article, the authors analyze citizens' reactions to Brexit on social media after the referendum results by performing a content analysis of 5877 posts collected from the social media platform Flickr, written in English, German, French, Spanish or Italian. Their research aims to answer the three following questions: What multimodal practices are adopted by citizens when they react to societal events like Brexit? To what extent do these practices illustrate types of citizenship that are specific to social networks? Can we observe different reactions to Brexit according to the languages used by the citizens? The authors focus on the types of visual content the citizens used to react to Brexit, as well as on what types of social relations this content can particularly create between their authors and the other members of the Flick community. Their article also highlights to what extent these posts shared on Flickr show content that is in favour of, or against, Brexit.